2021
DOI: 10.1038/s41420-021-00513-0
|View full text |Cite
|
Sign up to set email alerts
|

P300/HDAC1 regulates the acetylation/deacetylation and autophagic activities of LC3/Atg8–PE ubiquitin-like system

Abstract: Protein acetylation plays potential roles in regulating autophagy occurrence. However, it varies greatly between yeast and mammals, and has not been thoroughly investigated in other organisms. Here, we reported that the components of BmAtg8–PE ubiquitin-like system (BmAtg3, BmAtg4, BmAtg7, and BmAtg8) in Bombyx mori were localized in the nucleus under nutrient-rich conditions, whereas they were exported to the cytoplasm upon autophagy induction. RNAi of BmP300 and inhibition of BmP300 activity resulted in nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In addition, the acetylation levels of Atg proteins from LC3/ BmAtg8-PE ubiquitin-like protein system are increased by histone acetyltransferase P300 while decreased by deacetylase HDAC1 in B. mori and human. Subsequently, deacetylation of the Atg proteins mediated by HDAC1 leads to their nucleocytoplasmic translocation and autophagy occurrence (Popelka and Klionsky, 2015;Wu et al, 2021a). These results show that the regulatory mechanism of acetylation in regulating autophagy is highly conserved in B. mori and mammals (Wu et al, 2021b).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, the acetylation levels of Atg proteins from LC3/ BmAtg8-PE ubiquitin-like protein system are increased by histone acetyltransferase P300 while decreased by deacetylase HDAC1 in B. mori and human. Subsequently, deacetylation of the Atg proteins mediated by HDAC1 leads to their nucleocytoplasmic translocation and autophagy occurrence (Popelka and Klionsky, 2015;Wu et al, 2021a). These results show that the regulatory mechanism of acetylation in regulating autophagy is highly conserved in B. mori and mammals (Wu et al, 2021b).…”
Section: Discussionmentioning
confidence: 82%
“…Loss-of-function mutations of the acetylation sites lead to deacetylation and nucleo-cytoplasmic translocation of the four Atg proteins, and thereby promotion of autophagy. Collectively, acetylation/deacetylation of the molecular components from BmAtg8-PE ubiquitin-like protein system catalyzed by P300/HDAC1 mediates the occurrence of autophagy and is highly conserved from insects to mammals (Wu et al, 2021a).…”
Section: Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings of these studies altogether, VPA is likely to inhibit the mTOR pathway, dephosphorylating the HDAC1 [41]. This would prevent the translocation of HDAC1 into the nucleus, increasing acetylation of Atg4b, which is unlikely to catalyze the LC3/Atg8-PE required for autophagosome maturation [42]. The decreased autophagosome would eventually increase the stability of CCN1 protein, increasing the overall activity of CCN1 to promote osteogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Wu and his colleagues (2021) demonstrated that the mTOR pathway is activated by cholesterol derivatives that phosphorylate HDAC1 [41]. HDAC1 deacetylates autophagy-related protein 4b (Atg4b), which catalyzes the ubiquitin-like system, LC3/Atg8-phosphatidylethanolamine (PE), to generate autophagosome for degrading various cellular components [42]. Based on the findings of these studies altogether, VPA is likely to inhibit the mTOR pathway, dephosphorylating the HDAC1 [41].…”
Section: Discussionmentioning
confidence: 99%